Dramatic resolution of bullous pemphigoid after surgery for gastric cancer: A case report - Noguchi, Keita; Kawamura, Hideki; Ishizu, Hiroyuki; Okada, Kuniaki (International Journal of Surgery Case Reports, 2014)
An association between bullous pemphigoid (BP) and internal malignancy has been suggested. However, no reports have documented a dramatic improvement in BP after surgery for gastric cancer. An 82-year-old Japanese woman was admitted to a local hospital for severe fatigue. On examination, she was diagnosed with BP and gastric cancer. Her BP was resistant to steroid treatment; however, it improved dramatically after surgery for gastric cancer. In this case, a strong relationship appeared to exist between BP and gastric cancer. This is the first report of a dramatic improvement in BP after surgery for gastric cancer.